2012
DOI: 10.1523/jneurosci.0194-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Activity Promotes Synapse Formation in a Cell-Type-Dependent Manner in the Developing Retina

Abstract: Spontaneous activity is thought to regulate synaptogenesis in many parts of the developing nervous system. In vivo evidence for this regulation, however, is scarce and comes almost exclusively from experiments in which normal activity was reduced or blocked completely. Thus, whether spontaneous activity itself promotes synaptogenesis or plays a purely permissive role, remains uncertain. In addition, how activity influences synapse dynamics to shape connectivity and whether its effects among neurons are uniform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 85 publications
(146 reference statements)
2
63
1
1
Order By: Relevance
“…Before mating, both mouse lines had been crossed into a C57BL/J6 background for more than five generations. To probe the function of NGL-2 in retinal development, we compared mice lacking the coding exon of the Ngl-2 gene, which is alternatively referred to as Leucine-rich repeat containing 4 (Lrrc4 ) in the literature, in a mixed B6/129S5 background (Ngl-2 Ϫ/Ϫ mice; B6;129S5-Lrrc4 tm1Lex / Mmucd; Mutant Mouse Regional Resource Centers, University of California, Davis, Davis, CA) (Tang et al, 2010) to wild-type littermates (WT). Throughout this study postnatal day 0 (P0) was defined as the day of birth and results from mice of both sexes were combined.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Before mating, both mouse lines had been crossed into a C57BL/J6 background for more than five generations. To probe the function of NGL-2 in retinal development, we compared mice lacking the coding exon of the Ngl-2 gene, which is alternatively referred to as Leucine-rich repeat containing 4 (Lrrc4 ) in the literature, in a mixed B6/129S5 background (Ngl-2 Ϫ/Ϫ mice; B6;129S5-Lrrc4 tm1Lex / Mmucd; Mutant Mouse Regional Resource Centers, University of California, Davis, Davis, CA) (Tang et al, 2010) to wild-type littermates (WT). Throughout this study postnatal day 0 (P0) was defined as the day of birth and results from mice of both sexes were combined.…”
Section: Methodsmentioning
confidence: 99%
“…The density recovery profile (DRP) of HC somata was calculated following the definition of Rodieck (1991) using previously described routines (Soto et al, 2012). Briefly, the density of HCs was measured in 5-m-wide annuli at increasing distance from a reference cell, with each HC in an image serving once as the reference cell.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, recent studies have indicated that the development of some retinal microcircuits may be sensitive to activity, whereas other are not (Kerschensteiner et al 2009;Elstrott and Feller 2010;Xu et al 2010;Soto et al 2012). These data suggest that perhaps as subsets of retinal microcircuits emerge, the maturation of inhibitory synapses exerts a more powerful influence on the structure of correlated activity.…”
Section: Discussionmentioning
confidence: 99%
“…This spontaneous activity is necessary for refinement of retinal ganglion cell (RGC) axons within target regions of the brain (for reviews, see Guido 2008 andHuberman et al 2008). In addition, there is growing evidence that retinal waves may play a role of the stratification of dendrites of a subset of RGCs (Xu et al 2010) as well as in the synaptic maturation of particular retinal circuits (Kerschensteiner et al 2009;Soto et al 2012).…”
mentioning
confidence: 99%